EVALUATION AFFECTING FACTORS OF THE EARLY DETECTION OF OPTIC NERVE ATROPHY - Васюта, В.А. (World of Medicine and Biology, 2015)
The problem of the origin and progression of optic atrophy (ONA), despite numerous attempts to solve the scientific community remains socially relevant and meaningful. ONA - polietiological disease that requires a comprehensive approach taking into account history (presence of severe somatic diseases, hypertensive syndrome), data of laboratory and instrumental investigations, consultation with experts of related professions (neurologist, neurosurgeon, cardiologist, etc.). Objective. To study the main factors affecting the early detection of ONA. Materials and methods. We analyzed medical records and history, standard ophthalmologic research conducted to identify ONA: study visual acuity, direct and reverse ophthalmoscopy, biomicroscopy, computer perimetry. Patients were divided into 2 groups. The first group (330) - patients with a rising ONA (a consequence of ophthalmic diseases), the second group (1667) - patients with descending ONA (consequence of the diseases of central nervous systemat). Evaluated residence in urban areas, completeness ophthalmologic, general clinical investigations, completeness advice and collecting history. For the purpose of extrapolating the results to the general population was defined confidence interval of 95% probability assessment. To determine the statistical significance of the difference in the comparison group was used Pearson x2 test. For prognostic evaluation parameters that affect the likelihood of early detection of ascending and descending forms ONA spent determining the odds ratio with 95% confidence interval (95% CI) and assessment of the impact of heterogeneous factors (I2). Results. Analysis of the results showed a significant difference for the studied parameters in different types of ONA and residents in villages and towns. More late diagnosis of ONA observed in villagers (in up to 3 months turns 28,6% of rising ONA and 3,3% downward ONA), the inhabitants of the cities, these figures are 59,5 and 8,9% respectively. The situation with a longer diagnosis ascending ONA villagers due to the lower availability of high quality medical care for rural residents. Living in a city increases the likelihood of early diagnosis of ascending ONA in 3,67 times, the availability of a complete eye examination at 4,03 times, full general clinical examination - in 3,05 times (p